Serious Concern of Congenital Zika Syndrome (CZS) in India: A Narrative Review - Maneesh Kumar; Suman Kumar; Ratnesh Kumar; Mithilesh Kumar Jha; Shashank Nand Tiwari; Pratima Gupta (Journal of Pregnancy)
Congenital Zika syndrome (CZS) is a major concern in India and highlights the multifaceted challenges posed by the Zika virus (ZIKV). The alarming increase in CZS cases in India, a condition that has serious effects on both public health and newborns, has raised concerns. This review highlights the importance of raising concern and awareness and taking preventive measures by studying the epidemiology, clinical symptoms, and potential long-term consequences of CZS. The review also contributes to worldwide research and information sharing to improve the understanding and prevention of CZS. As India deals with the changing nature of CZS, this thorough review is an important tool for policymakers, health workers, and researchers to understand what is happening now, plan for what to do in the future, and work together as a team, using medical knowledge, community involvement, and study projects to protect newborns’ health and reduce the public health impact of these syndromes.